Characterization of the complete mitochondrial genome of the tea leaf roller Caloptilia theivora (Insecta: Lepidoptera: Gracillariidae). Issue 2 (3rd July 2019) - Chen, Shi-Chun; Jiang, Hong-Yan; Shang, Jing; Hu, Xiang; Peng, Ping; Wang, Xiao-Qing
Abstract: The tea leaf roller, Caloptilia theivora (Walsingham), is a serious pest of tea plants. We have obtained and annotated the complete mitochondrial genome of C. theivora (GenBank accession No. MK541932). The entire mt genome is 15, 297 bp long with an A + T content of 80.66%. The mt genome of C. theivora encodes all 37 genes that are typically found in animal mt genomes, consists of 13 protein-coding genes, 2 ribosomal RNA, and 22 transfer RNA genes. The gene order is consistent with other moths mt genome in Ditrysia. The control region of this genome is 192 bp long with a high A + T content of 96.35%, and located between the rrnS and trnI genes. Phylogenetic analysis was performed using 13 protein-coding genes among 19 moths showed that C. theivora is closely related to species of Gracillariidae.